Unified model for hollow columns externally confined by FRP. (15th March 2016) - Cascardi, Alessio; Micelli, Francesco; Aiello, Maria Antonietta
Abstract: Nowadays, the employment of Fibre Reinforced Polymer (FRP) composites in civil engineering field has been successfully experienced. Different potential applications of solid concrete-filled FRP tubes are exploitable in marine piles, overhead sign structures, poles and posts, bridge columns and piers, girders, large pipes and tunnels (mainly circular cross-section). This technique is also used for the confinement of masonry columns, typically encountered in monuments and historical buildings (both rectangular and circular cross-section); hence the need of providing formulas for the design of an appropriate strengthening. Several analytical models are available in the scientific literature for assessing the increase of strength and ductility of concrete or stone solid elements externally confined with FRP or for hollow columns internally steal enclosed and externally FRP-confined but, there is still a lack of research about hollow columns only externally confined. The presence of an empty core implies a different stress state in the inner cylindrical surface with respect to the outer one. Inwards deformations are more significant and this behaviour is not taken into account by available models. The present study aims to illustrate a detailed summary of the existing analytical models and to provide a unified procedure for concrete and masonry hollow columns valid for both circular and square cross-sections. An iterative method that updates the geometrical parameters according to step-by-step uniaxial compressed column is shown in order to capture the real deforming behaviour of the compressed solid. This analytical approach has two important implications: the first is the ability of calculating the stress state of the column and of the external FRP reinforcement at each step; the second is that of theorizing a procedure, which is independent on the type of material used for the column. The outputs of the proposed method are then compared with experimental results currently available in the scientific literature. A good matching is obtained between the available experimental results and the analytical predictions in term of axial stress–strain curves.